Strategi Keberlanjutan Bisnis: Tinjauan Literatur Sistematis - Nurdin I Muhammad; Abdul Hadi Sirait; Abdul Chalid Ahmad; Abdullah W Jabid (Society, 2025)
The current systematic literature review is intended to capture the extent of research on business sustainability strategy. Using PRISMA, a systematic search was conducted on Scopus and WoS databases published between January 2010 and October 2024, resulting in 3 articles that met the inclusion criteria. The synthesis results of these articles indicate that business sustainability strategy has been carried out in the kibbutz industry, human resources, and sector specialization based on mergers and acquisitions. In addition, research results were also collected in the agriculture and military, manufacturing, and services industries. Furthermore, contingency theory is one of the theories used to explain this relationship. This study provides theoretical and practical contributions as well as directions for future research.